Bone mineral density and vertebral compression fracture rates in ankylosing spondylitis. Issue 2 (February 1994) - Donnelly, S; Doyle, D V; Denton, A; Rolfe, I; McCloskey, E V; Spector, T D
Abstract : OBJECTIVE--To examine the relationship between disease severity and bone density as well as vertebral fracture risk in patients with ankylosing spondylitis (AS). METHODS--Measurements were taken for bone mineral density (BMD) and vertebral fracture rates in 87 patients with AS. BMD was measured at the hip (femoral neck -FN), lumbar spine (L1-L4-LS) and for the whole body using a hologic-QDR-1000/W absorptiometer. An algorithm based on normal female ranges of vertebral heights was used to define a fracture as occurring when two vertebral ratios were each three standard deviations below the calculated mean of the controls. RESULTS--Patients with AS had significantly lower FN-BMD in proportion to disease severity (based on a Schober index) and disease duration. LS-BMD was also reduced in early disease, but in patients with advanced AS it had increased considerably. Nine vertebral fractures (10.3%) were identified which was considerably higher than expected when compared with a fracture of 1.9% in a control population of 1035 females of a similar age range. Patients with AS with fractures were significantly older, more likely to be male, had longer disease duration and more advanced spinal limitation with less mobility. There was no significant reduction in lumbar spine or femoral neck bone density in the fracture group. CONCLUSIONS--Vertebral fractures that result from osteoporosis are a feature of longstanding AS. BMD used as a measure of osteoporosis of the spine in advanced AS is unreliable probably as a result of syndesmophyte formation and does not predict the risk of vertebral fracture. Alternative sites such as the neck of the femur should be used for sequential assessment of BMD in AS.